Brief introduction of animal experiment registration platform - YI Shaowei; WANG Zhe; RUAN Jianhua; HU Kaiyan; AO Qi; REN Ziyu; ZHAO Yue; DING Fengxing; LIU Chen; LIU Yanli; LI Zhaoxia; MA Bin (Yixue xinzhi zazhi)
Preclinical animal experiment is an important bridge connecting basic medicine and clinic, and the necessity of animal experiment registration is becoming more and more apparent. This paper introduces the international animal experiment registration platform, registration content and process, and compares and analyzes it, aiming to popularize the knowledge of animal experiment registration, improve the awareness of researchers, and provide reference for domestic researchers to register animal experiments.